La problematica geopolitica dei separatismi nel labirinto della sovranità - Barbaro, Francesco (Studi Politici, 2023)
This paper aims to address the issue of separatisms, finally offering it a geopolitical perspective. The topic, in fact, has so far not found adequate treatment in the field of geographic-political studies, seeing instead approaches from the juridical area prevail. The latter have focused more on questions oof separatist movement’s moral legitimacy and procedural propriety. In this way, however, the spatial reason that constitutes their foundation, and in which the ultimate meaning of their very problematic nature is encapsulated, has been entirely left out. The article moves precisely from the recognition of said spatial reason, identified in the historically recurring opposition between territorially hegemonic and antagonistic powers. Its juridical-political translation, in which the principles of territorial integrity and peoples’ self-determination are at odds, causes proponents of both to get lost in the “labyrinth of sovereignty”. By analyzing various spatial dichotomies of power, we propose to overcome this dialectic with an “amphibious” synthesis based on the function of governance.